Pengaruh Good University Governance dan Manajemen Risiko terhadap Kinerja Perguruan Tinggi Negeri di Indonesia - Syahrir, Azhar; Siregar, Hermanto; Fahmi, Idqan; Mulyati, Heti (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The performance achievement of State Universities (PTN) in Indonesia is measured based on Key Performance Indicators (KPIs) regulated in the Minister of Education and Culture's Decree Number 3 of 2021. The evaluation results for the year 2020 indicate that a significant portion of PTN's performance has not yet met the expected outcomes. The implementation of the Good University Governance (GUG) model and Risk Management in PTN is still limited in the existing literature. The research's objective is to examine the relationship between the implementation of GUG and Risk Management on the performance of PTN. The method employed is the Structural Equation Model based on variance, namely Partial Least-Squares. The analysis results are effective implementation of GUG enhances the quality of the curriculum and learning, as well as improves the governance quality of PTN. Additionally, Risk Management implementation has a positive impact on enhancing the quality of higher education graduates.